Africa's Pulse, October 2012 : An Analysis of Issues Shaping Africa's Economic Future - World Bank (Washington, DC, 2014)
This Africa's pulse newsletter includes the following headings: Sub-Saharan African countries continue to grow at a steady pace; the region's decade-long economic expansion appears sustainable; and for newly resource-rich countries, strong governance will be key to harnessing resource wealth for development.